Стратегічні напрями розвитку взаємодії влади, бізнесу та суспільства в галузях соціальної інфраструктури в індустріальних регіонах України - Василенко, Т.Д. (Стратегія і механізми регулювання промислового розвитку, 2014)
Pозглянуто стан та фінансування галузей соціальної інфраструктури в індустріальних регіонах України: Донецькій, Дніпропетровській, Запорізькій, Луганській областях. Визначено проблеми цих галузей та шляхи їх вирішення через взаємодію влади, бізнесу та суспільства. Рассмотрены состояние и финансирование отраслей социальной инфраструктуры в индустриальных регионах Украины: Донецкой, Днепропетровской, Запорожской, Луганской областях. Определены проблемы этих отраслей и пути их решения через взаимодействие власти, бизнеса и общества. The article reviews the status and funding of social infrastructure sectors in industrialized regions of Ukraine, Donetsk, Dnepropetrovsk, Zaporozhye and Lugansk regions. The state of health care and the cost of the industry compared to developed countries. Determined dramatic changes in the educational system of Ukraine: preschool education; secondary, vocational and higher education. The problems areas of social infrastructure and solutions through the interaction of government, business and society. Solved constraints of interaction between government, business and society; strengths and weaknesses of the business partnership. Analyzed the financial resources of each of the partners. The experience and implemented mechanisms of cooperation between government, business and society in industrialized regions.